Cost Analysis of Antibiotics Utilization in Emergency Department and Other Wards: A Comparative Study - Kumar, Shiv; Paul, Fransty; Davis, Alfi Mariya (Indian Journal of Pharmacy Practice)
Background: An excessive amount of antibiotics is prescribed, which not only adds to the problem of antibiotic resistance but also exposes patients to their negative effects and raises the expense of medical care. Healthcare professionals are considering more complete models for making medical decisions because of medical, ethical, and societal concerns regarding the costs and quality of care associated with antibiotics. This study aims to estimate and compare the cost of antibiotics drugs in the emergency departments and wards of a private tertiary care hospital. Materials and Methods: A comparative prospective observational study was conducted for six months in Navodaya Medical College, Hospital, and Research Center with a sample size of 180. Data were collected from all hospitalized patients who are admitted to the emergency department and another ward with chronic diseases in the hospital during the study period. Results: In the emergency department, Penicillin was the most expensive class of antibiotics 30% (9165rs) and in other words, carbapenem was the most expensive class of antibiotics 40% (16448rs). Of 90 patients, In the emergency department, piperacillin/tazobactam was the most expensive antibiotic which was 29.94% (9075rs), and of 90 patients in other ward meropenem was the most expensive antibiotic with 40% (16448rs). Conclusion: A high cost of treatment was noticed, comparable to other published data. Regular prescription audits and modifications of antibiotics policy are required to curtail the inapt use of antibiotics and the economic burden of hospitals.
Keywords: Cost analysis; Antibiotic; Emergency department; Other Wards